Pengaruh Self-Efficacy dan Self-Esteem terhadap Kepuasan Kerja - Aprilya, Dewa Ayu Zendyana; Sadiartha, A.A Ngurah Gede; Saputra, Gusti Alit (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
In a company the most important thing to have is Human Resources (HR) in order to achieve its goals. As in this era of globalization, both private and government agencies will definitely need quality human resources to meet the company’s performance and targets. The purpose of this study was to determine the effect of self-efficacy and self-esteem on job satisfaction of contract employees at the General Section of the Regional Secretariat of Badung Regency. The research was conducted at the General Section of the Badung Regency Secretariat which is located at Jl. Raya Sempidi, Mengwi District, Badung Regency. And the sample used was 47 respondents. The data analysis technique used is the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Coefficient of Determination Test, t test and f test. Based on the results of the study it can be seen that self-efficacy has a positive and partially significant effect on job satisfaction at the General Section of the Badung Regency Regional Secretariat, Self-esteem has a positive and partially significant effect on job satisfaction at the General Section of the Badung Regency Regional Secretariat, Self-efficacy and Self-esteem has a simultaneous effect on job satisfaction at the General Section of the Regional Secretariat of Badung Regency. The magnitude of the influence of independent variables on employee job satisfaction is 66.4%. The advice that can be given by researchers is that leaders must provide good motivation so that employees are more enthusiastic about facing existing obstacles, employees must be more aware of their potential, and for agencies to pay more attention to their employees, especially for employees who have worked for a long time so that there is career advancement. in the future so as to increase customer satisfaction.